Unitization and securitization of property investment: Implications for future valuation - Tajudeen, Aluko Bioye; Abel, Olaleye (Journal of Business Economics and Management, 2005)
Property investments are now mobile, being tradable securities or listed units (vehicles) comparable to stocks/ shares in the financial market. Hence, the need for valuation to be a counterpart to investment and security analysis. But, current valuation practice in the country has not placed property in a wider economy and the analytical techniques of other markets. The paper therefore demonstrates how current valuation techniques in the property market can meet the needs of investors for listed or tradeable property assets in the country. It also examines the implications on the valuation profession as well as the attendant consequences that are likely to be associated with the quest for change. The study utilizes data from both the Nigerian property and capital markets using simple descriptive, non‐statistical, techniques. First published online: 14 Oct 2010